TEKNIK KOMUNIKASI GURU PADA PENYANDANG DISABILITAS TUNADAKSA DALAM MENDAMPINGI MELEK AKSARA PESERTA DIDIK - Raihanah, Raihanah (Titik Fokus Karya, 2023)
Communication is not just about talking; it also involves life experiences, thought patterns, and imagination. Therefore, when teaching children with special needs, teachers employ different communication techniques. This research aims to explore the communication techniques used by teachers to enhance literacy in children with physical impairments, along with the supporting and inhibiting factors involved. This study employs a qualitative descriptive case study approach. The research subjects included homeroom teachers, special education (ABK) support teachers, and children with physical impairments at SDIT Al-Firdaus Banjarmasin. Data collection methods included observation, interviews, and documentation. The findings reveal that the communication techniques used by teachers to enhance literacy include informative communication, persuasive communication, instructive communication, and human relations communication. The supporting factors for teacher communication in promoting literacy include internal aspects such as the teacher’s mood, intonation, and facial expressions. External supporting factors include children's intellectual abilities, responsiveness, ethics, and manners, as well as the availability of facilities and infrastructure. Inhibiting factors are categorized as internal, such as educational background, experience, and teacher training, and external, such as children's moods, health conditions, and the challenges of distance learning.